Cross‐border analysis of China– Pakistan Economic Corridor development project and local residence quality of life. Issue 2 (12th September 2019) - Kanwal, Shamsa; Pitafi, Abdul Hameed; Ahmad, Mudaser; Khan, Naseer Abbas; Ali, Syed Muhammad; Surahio, Muhammad Kashan
Abstract : China–Pakistan Economic Corridor (CPEC) is a megaproject, which directly and indirectly benefits the local community of two countries, namely, Peoples' Republic of China and Pakistan. The purpose of current research is to investigate the impact of CPEC development on the quality of life of local residents in China and Pakistan. We intend to investigate the perceptions of local community related to CPEC development, as policymakers of both countries argue the CPEC to be equally beneficial for the people of China and Pakistan. To test the proposed hypotheses, we collected primary data through a research survey conducted in Pakistan and China. In total, 410 Chinese respondents and 480 Pakistani respondents were included in the study. Most of the hypotheses were supported in both studies showing the positive attitude of the people of both communities towards CPEC project. Specifically, the perceived impact of CPEC has shown a significant effect on employment and quality of life in both samples. This research provides important suggestions and recommendations.